2005
DOI: 10.1249/01.mss.0000169611.21671.2e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cryotherapy after Contusion Using Real-Time Intravital Microscopy

Abstract: Our results suggest that local tissue cooling, similar to cryotherapy, improves edema and inflammatory reaction, and may be useful for reducing inflammatory response without inhibiting blood flow after contusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 22 publications
1
46
1
1
Order By: Relevance
“…By contrast, Gregson et al (2013) observed that 10 min of immersion in cold water (8°C) did not alter muscle glycogen resynthesis following endurance exercise. Several animal studies have demonstrated that icing after muscle injury reduces markers of inflammation and oxidative stress in muscle (Hurme et al, 1993;Lee et al, 2005;Carvalho et al, 2010;Puntel et al, 2011;Takagi et al, 2011). However, in partial support of our findings, Takagi et al (2013) found that icing attenuated muscle fibre regeneration and caused greater fibrosis 4 weeks after muscle crush injury.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By contrast, Gregson et al (2013) observed that 10 min of immersion in cold water (8°C) did not alter muscle glycogen resynthesis following endurance exercise. Several animal studies have demonstrated that icing after muscle injury reduces markers of inflammation and oxidative stress in muscle (Hurme et al, 1993;Lee et al, 2005;Carvalho et al, 2010;Puntel et al, 2011;Takagi et al, 2011). However, in partial support of our findings, Takagi et al (2013) found that icing attenuated muscle fibre regeneration and caused greater fibrosis 4 weeks after muscle crush injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing body of evidence from animal and human models highlighting a key role for inflammation in promoting adaptive and regenerative responses to muscle injury (Lee et al, 2005;Takagi et al, 2011;Paulsen et al, 2012). The eccentric component of traditional resistance causes micro-damage, localised inflammation and tissue oedema (Clarkson et al, 1986).…”
Section: Exercise Recovery and Cold Water Immersionmentioning
confidence: 99%
See 3 more Smart Citations